2017
DOI: 10.3389/fpls.2017.01445
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Is Involved in β-Cyclodextrin-hemin Complex-Induced Lateral Root Formation in Tomato Seedlings

Abstract: Although previous results showed that β-cyclodextrin-hemin complex (β-CDH) could induce tomato lateral root (LR) formation, the corresponding downstream messengers are still not fully understood. In this report, similar to the inducing effects of exogenously applied hydrogen peroxide (H2O2), we discovered that β-CDH elicited RBOH1 transcript upregulation, endogenous H2O2 accumulation, and thereafter tomato LR development. Above responses were sensitive to dimethylthiourea (DMTU) and ascorbic acid (AsA), two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The expression changes of these genes were in line with changes in the levels of phytohormone. For instance, GRMZM5G809195 encoded an IAA14 protein, which is a member of the Aux/IAA protein family, involved in the regulation of lateral root development [35,36]. GRMZM2G078465 encoded an indole-3-acetate beta-glucosyltransferase, which catalyzes the conjugation of IAA with glucose, contributing to the homeostasis of phytohormone in plant [37].…”
Section: Discussionmentioning
confidence: 99%
“…The expression changes of these genes were in line with changes in the levels of phytohormone. For instance, GRMZM5G809195 encoded an IAA14 protein, which is a member of the Aux/IAA protein family, involved in the regulation of lateral root development [35,36]. GRMZM2G078465 encoded an indole-3-acetate beta-glucosyltransferase, which catalyzes the conjugation of IAA with glucose, contributing to the homeostasis of phytohormone in plant [37].…”
Section: Discussionmentioning
confidence: 99%
“…Hemin is the purified form of natural Heme in vitro, which is generally isolated and purified from animal blood. Hemin is a simple metal porphyrin compound formed by a complex comprising ferrous and protoporphyrin molecules [ 17 ]. It has been reported that Hemin acts as an inducer of heme oxygenase-1 (HO-1) at the transcriptional, translational and post-transcriptional levels [ 18 ], and can be used as a highly effective inducer to alleviate the damage caused by abiotic stresses (heavy metals, salinity, drought, etc.)…”
Section: Introductionmentioning
confidence: 99%